2016
DOI: 10.1126/science.aak9762
|View full text |Cite
|
Sign up to set email alerts
|

Parsing reward from aversion

Abstract: Investigating the neural circuits encoding emotional valence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Over 50 years of comparative research with animals and humans has yielded general agreement regarding principal functions of these circuits in mediating approach and avoidance emotions and motivating approach and avoidance behaviors (see Beauchaine & Zisner, 2017). It should be noted, however, that subcortical neural systems are structurally interconnected and functionally interdependent (see Beauchaine & Constantino, 2017; Beyeler, 2016; Corr, 2013). For example, the nucleus accumbens (a ventral striatal structure) and the amygdala share interconnections via the paraventricular nucleus and the stria terminalis (e.g., Dong, Li, & Kirouac, 2017).…”
Section: Neural Models Of Emotion Dysregulation I: Evolutionary Functmentioning
confidence: 99%
“…Over 50 years of comparative research with animals and humans has yielded general agreement regarding principal functions of these circuits in mediating approach and avoidance emotions and motivating approach and avoidance behaviors (see Beauchaine & Zisner, 2017). It should be noted, however, that subcortical neural systems are structurally interconnected and functionally interdependent (see Beauchaine & Constantino, 2017; Beyeler, 2016; Corr, 2013). For example, the nucleus accumbens (a ventral striatal structure) and the amygdala share interconnections via the paraventricular nucleus and the stria terminalis (e.g., Dong, Li, & Kirouac, 2017).…”
Section: Neural Models Of Emotion Dysregulation I: Evolutionary Functmentioning
confidence: 99%
“…However, evolution created a separate process for punishment, and while it may seem redundant, 5-HT has been known to play a critical role in punishment. It is found that approximately 90% of 5-HT is secreted by gut chromaffin cells in response to noxious food, thus inducing vomiting or diarrhea (Beyeler, 2016; Zheng et al, 2016). Some plants exploit this function of 5-HT by expediting passage of seed through the digestive system.…”
Section: Biological Aspects Of Emotionsmentioning
confidence: 99%
“…In addition, some animals such as scorpion and wasp stings also use 5-HT to induce pain (Gu et al, 2016). Aversion is separated from reward in the evolutionarily lower animals (Beyeler, 2016). The nematode, Caenorhabditis elegans , can also be infected by pathogenic bacteria, even though it feeds on bacteria.…”
Section: Biological Aspects Of Emotionsmentioning
confidence: 99%